SELEKSI SAHAM DENGAN MODEL CAPITAL ASSET PRICING MODEL (CAPM) - Rakhman, Ani Rakhmanita; Nugraha; Maya Sari; Desy Tri Anggarini (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This research was motivated by the Covid-19 pandemic, where the pandemic had amajor influence on the condition of the Indonesian capital market. Investors arevery careful in deciding investments from the possibilities they will face. Thepurpose of this research is to select efficient property and consumer good stocksduring the COVID-19 pandemic by using the Capital Asset Pricing Model. Thisstudy uses a descriptive quantitative approach. The sample used is the monthlyshares of the largest property companies in Indonesia and food and beveragecompanies in the 2016 - 2020 period. The data used in this study is secondary datataken from the Indonesia Stock Exchange and Bank Indonesia. The results of thisstudy indicate that the 8 companies studied, 1 company is in an efficient conditionand 7 companies are in an inefficient condition. Investment decisions that must betaken during a pandemic require accuracy, sufficient knowledge, experience andbusiness instincts from investors in deciding which shares to buy, to sell, and tohold.